THE FUTURE OF SUSTAINABLE AGRICULTURE INVESTIGATING MULTIDIMENSIONAL APPROACHES TO ENVIRONMENTAL, SOCIAL, AND ECONOMIC SUSTAINABILITY - Pande Wayan Renawati; Karan Singh; Lucy Kanai (Yayasan Adra Karima Hubbi, 2026)
Sustainable agriculture has become a global imperative in response to climate change, resource depletion, biodiversity loss, and rural socioeconomic inequality. Conventional productivity-driven models have increasingly been criticized for neglecting environmental integrity and social equity. Multidimensional approaches integrating environmental, social, and economic sustainability are therefore gaining prominence; however, empirical evaluation of their combined performance remains limited. This study aims to investigate the effectiveness of integrated sustainability models in agricultural systems and to examine the interactions among environmental restoration, social inclusion, and economic viability. A mixed-methods design was employed involving 150 farms categorized into conventional, agroecological, and regenerative systems across diverse agroecological regions. Quantitative data were collected through composite sustainability indices measuring soil health, biodiversity, labor conditions, income stability, and market diversification, complemented by qualitative stakeholder interviews. Multivariate and structural analyses were conducted to assess relationships and comparative performance. Results indicate that regenerative and agroecological systems significantly outperform conventional models in environmental and social sustainability while maintaining stable economic outcomes. Strong positive correlations among sustainability dimensions suggest synergistic rather than trade-off effects. The findings support systemic, multidimensional frameworks as viable pathways toward resilient and equitable agricultural futures.